2021
DOI: 10.1002/elan.202100314
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Monolayer Doping PEDOT : PSS Janus Film for Hydrogen Sulfide Sensor

Abstract: AuNPs monolayer doping Poly(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT : PSS) film on interdigitated electrode had been fabricated into AuNPs/PEDOT : PSS Janus film sensor to detect hydrogen sulfide (H 2 S). The results show that the Janus film sensors have a wide measurement range of H 2 S concentration. The sensitivity of PEDOT : PSS/AuNPs sensor grows up with the thickness of Janus film increases. The resistance response of AuNPs Janus film was affected little by the rough surface states of PED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…As we all know, thiol (R-SH) easily forms a strong Au-S bond with Au, [1,43] and H 2 S has a similar structure to R-SH, which can be inferred Au and H 2 S also form a similar structure. [39] During the synthesis of AuNWs, the OAm was initially used as a growth template and finally formed Au-OAm complexes with Au through the NH 2 group, [26] and in this process, OAm also acted as the solvent, reducing agent, and surface capping agent with protecting the AuNWs. [1] According to thermodynamic knowledge, H 2 S needs to form a more stable structure to adsorb on AuNWs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we all know, thiol (R-SH) easily forms a strong Au-S bond with Au, [1,43] and H 2 S has a similar structure to R-SH, which can be inferred Au and H 2 S also form a similar structure. [39] During the synthesis of AuNWs, the OAm was initially used as a growth template and finally formed Au-OAm complexes with Au through the NH 2 group, [26] and in this process, OAm also acted as the solvent, reducing agent, and surface capping agent with protecting the AuNWs. [1] According to thermodynamic knowledge, H 2 S needs to form a more stable structure to adsorb on AuNWs.…”
Section: Resultsmentioning
confidence: 99%
“…To study the influence of H 2 S on the conductivity of AuNWs, 10 μL of the AuNW solution mentioned was dropped above on a 1 × 1 cm 2 interdigital electrode. The interdigitated electrode has twenty interdigital electrodes (ten electrodes for each polarity, for detailed information refer to [ 39 ] ), each electrode is 100 μm wide, and the distance between the two electrodes is 100 μm. After the chloroform was volatilized, the multimeter showed that AuNWs were insulation (more than 40 MΩ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are quite promising for resolving issues such as sensitivity and high-temperature operation but still lack in achieving selectivity and swift operation of the sensor . In this regard, certain strategies have been discussed in the literature such as surface functionalization, formation of heterojunctions, zeolite filters, noble-metal decoration, etc. A promising strategy to overcome these limitations is to fabricate sensors based on heterostructures/hybrids from these pristine materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a conductive polymer (CP) hybridized and doped by noble metal nanoparticles (NPs) had been paid wide attention because NPs can provide additional absorption sites and promote a chemical reaction (chemisorption and redox). 4 The chemiresistive sensor working theory can be attributed to two main factors: (i) the presence of CPs (or NPs) leads to the release of protons by reacting with H 2 S and (ii) the formation or deformation of a metal−semiconductor junction leads to the amplification of the response to H 2 S. 1 However, there are few studies on the detection of H 2 S with a flexible and transparent film under the economizing noble metal nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%